Shock microcycle of repeated-sprint training in hypoxia and tennis performance: Case study in a rookie professional player - Brechbuhl, C.; Schmitt, C.; Millet, G. P.; Brocherie, F. (International Journal of Sports Science & Coaching, 2018)
The aim of this case study was to investigate the effects of a shock microcycle of repeated-sprint training in hypoxia (RSH) on physical fitness and tennis performance. One rookie professional tennis player performed repeated-sprint ability (RSA) and Yo-Yo Intermittent Recovery level 2 (YYIR2) tests before and after (+3 days and +21 days) six sessions of RSH (4 sets of 5?×?~6?s repeated-shuttle sprint interspersed by ~24 s of passive recovery) practiced during a 14-day "in-season" period. Tennis performance was subjectively measured from match results and Association of Tennis Professionals (ATP) points obtained during four professional tournaments played before and after intervention. While no changes were found at +3 days post-RSH, improvements in physical fitness (single sprint time (-4.5%), RSA total time (-3.1%) and sprint decrement (-16.7%), as well as YYIR2 total distance covered (+21.4%)) were observable at +21 days post-RSH. Tennis performance obtained during the tournaments was better after intervention. From pre to post-RSH, the decreases in opponents` ATP ranking during matches won (1109 ± 334 points vs. 818 ± 212 points) and lost (499 ± 68 points vs. 256 ± 58 points) revealed a stronger opposition. Consequently, a three-fold increase (from 4 to 12 ATP points gained from pre to post-RSH) in participant`s ATP ranking was recorded. In summary, a 14-day "in-season" shock microcycle including six sessions of repeated-sprint training in hypoxia revealed interesting effects in specific fitness and tennis performance in a rookie professional tennis player.